Nanostructures for peroxidases - Carmona-Ribeiro, Ana Maria; Prieto, Tatiana; NANTES, ISELI L. (Frontiers in Molecular Biosciences, 2015)
Peroxidases are enzymes catalyzing redox reactions that cleave peroxides. Their active redox centers have heme, cysteine thiols, selenium, manganese and other chemical moieties. Peroxidases and their mimetic systems have several technological and biomedical applications such as environment protection, energy production, bioremediation, sensors and immunoassays design and drug delivery devices. The combination of peroxidases or systems with peroxidase-like activity with nanostructures such as nanoparticles, nanotubes, thin films, liposomes, micelles, nanoflowers, nanorods and others is often an efficient strategy to improve catalytic activity, targeting and reusability.